Francis Bacon's Quasi-Materialism and its Nineteenth-Century Reception (Joseph de Maistre and Karl Marx) - Manzo, Silvia (2020)
This paper will address the nineteenth-century reception of Bacon as an exponent of materialism in Joseph de Maistre and Karl Marx. I will argue that Bacon's philosophy is "quasimaterialist". The materialist components of his philosophy were noticed by de Maistre and Marx, who, in addition, pointed out a Baconian materialist heritage. Their construction of Bacon's figure as the leader of a materialist lineage ascribed to his philosophy a revolutionary import that was contrary to Bacon's actual leanings. This contrast shows how different the contexts were within which materialism was conceived and valued across the centuries, and how far philosophical and scientific discourses may be transformed by their receptions, to the point that in many cases they could hardly be embraced by the authors of these discourses.